PELAKSANAAN PROGRAM #HOUSEPROJECT DALAM MENERAPKAN COMMUNITY BASED TOURISM DI DESA WISATA BANTARKARET BOGOR - Hasna, Andra Sahirah; Ridanti, Cut Fairi Auni; Etania, Dita Listya; Ardiyatna, Kadek Ayu Maharani (Universitas Islam Syekh Yusuf, 2022)
Many industries in Indonesia have been affected by the spread of the COVID-19 virus, particularly the tourism industry. Since then, the number of tourists visiting Indonesia has dropped significantly. One strategy to keep the tourism industry alive during the pandemic is to promote it through social media. Due to COVID-19 pandemic, the majority of the activities have to be done online, which supports the digital acceleration in Indonesia. The COVID-19 pandemic in Indonesia has impacted many things, including travel trends, where tourist destinations and attractions will focus more on the concept of Nature, Eco, Wellness, and Adventure (NEWA). A tourist destination that has this concept is a tourism village. One of the tourism villages that is categorized as a developing village is Bantarkaret Village. Bantarkaret Tourism Village aims to involve the community as tourism agents and administrators as a way of implementing community based tourism, which is a characteristic of a tourism village. This program focuses on giving photography, social media, and tourism planning training to the Bantarkaret Tourism Village local community in increasing competitiveness and productivity, and also preparing the community for the new normal era. The implementation of this program is guided by information processing theory and the stages of the tourism planning process model.